Flow shear stress applied in self-buffered microbial fuel cells. (December 2020) - Wang, Chin-Tsan; Ong Tang, Raymond Chong; Wu, Men-Wei; Garg, Akhil; Ubando, Aristotle T.; Culaba, Alvin; Ong, Hwai-Chyuan; Chong, Wen-Tong
Graphical abstract: Highlights: Performance enhancement of microbial fuel cells (MFCs) through shear stress. Higher shear stress supports better pH maintenance in the bufferless operation. COD removal increased with the intensity of flow shear stress. Flow shear stress shows a plausible implementation in bufferless operation. Abstract: The development of renewable and clean energy has been the priority of the global research field due to the urgent effects of climate change. Microbial fuel cell (MFC) is recognized as a sustainable approach to simultaneously generate power and treat wastewater through the employment of microorganisms as catalyst. The use of buffer solution in the wastewater treatment makes the commercial application of MFCs challenging due to their environmental impact and high costs. This work uses rotational motion to generate the flow stress in the anode chamber of the MFCs to enhance biofilm growth and mass transfer that leads to an overall performance improvement of the system. The effects on pH, chemical oxygen demand (COD), and power density were evaluated under rotational speeds of the magnetic stirrer from 0 to 640 rpm. The influence of the stirrer was then assessed utilizing the same parameters specified for scenarios with and without buffer. The results reveal that at 480 rpm of stirring speed, the pH value was neutral with a maximum COD removal of 82 % for bufferless and 93 % for buffered scenarios. In addition, for bufferless operation at 480 rpm yielded a power density of 402 mWm −2 . The results of the flow stress analysis for bufferless and buffered MFCs are beneficial for the commercialization and future development of the system for wastewater treatment applications.